1990
DOI: 10.1152/ajpregu.1990.258.2.r552
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gastrointestinal flora on body temperature of rats and mice

Abstract: The purpose of these experiments was to test the hypothesis that gut flora influences the body temperature of rodents. Rats and mice were implanted with biotelemetry transmitters that enabled us to record both abdominal temperature and activity for long periods of time. Rats given nonabsorbable antibiotics in their drinking water, which reduced their gut flora, had a marked decrease in both their daytime and nighttime temperatures. Similar results were found with germfree mice. The circadian rhythms in body te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 0 publications
2
28
1
Order By: Relevance
“…This difference in temperature was not related to the temperature in the animal rooms (all housed at 21°C room temperature) but was found to be related to the GI microbiota in BF mice, which was in accordance with a previous study. 15 In that study, Kluger and colleagues demonstrated that GI flora in BF-raised mice had a stimulatory effect on body temperature (unrelated to physical activity) compared with germfree mice. 15 In addition to the untreated SPF mice, we examined BF mice that were first treated with broad spectrum antibiotics, a widely established technique to significantly deplete the gut flora (supplemental Figure 2).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This difference in temperature was not related to the temperature in the animal rooms (all housed at 21°C room temperature) but was found to be related to the GI microbiota in BF mice, which was in accordance with a previous study. 15 In that study, Kluger and colleagues demonstrated that GI flora in BF-raised mice had a stimulatory effect on body temperature (unrelated to physical activity) compared with germfree mice. 15 In addition to the untreated SPF mice, we examined BF mice that were first treated with broad spectrum antibiotics, a widely established technique to significantly deplete the gut flora (supplemental Figure 2).…”
Section: Discussionmentioning
confidence: 98%
“…15 In that study, Kluger and colleagues demonstrated that GI flora in BF-raised mice had a stimulatory effect on body temperature (unrelated to physical activity) compared with germfree mice. 15 In addition to the untreated SPF mice, we examined BF mice that were first treated with broad spectrum antibiotics, a widely established technique to significantly deplete the gut flora (supplemental Figure 2). [28][29][30][31] We observed that after depletion of the GI flora in BF mice (supplemental Figure 2), their rectal temperatures remained static after housing for 1 week (Figure 1).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Both basal metabolic rate (Levenson et al 1969) and thermoregulatory setpoint (Kluger et al 1990) are lower in the germ-free animals, but can be restored through reconstitution of the normal enteric flora.…”
Section: The Indigenous Gut Floramentioning
confidence: 99%
“…Starch gives rise to more butyric acid, whereas non-starch polysaccharides result in a greater production of acetic and propionic acids (Pryde et al, 2002). In 1990 to 1991, Kluger and colleagues showed that germ-free rats produced by oral administration of bacitracin/ streptomycin had a significantly lower CBT than controls (Conn et al, 1991;Kluger et al, 1990). Their lower CBT was reversed by inoculation with spore-forming Gram-positive flora, prepared by 10 min heating cecal homogenate anaerobically collected from stock mice (Conn et al, 1991).…”
Section: Ucp1 Independent Thermogenesis a Cost-inefficient Means To mentioning
confidence: 99%